Anti-fatigue Ag / Al gradient nano multilayer structure metal film and preparation method thereof

The preparation of Ag/Al gradient nanomultilayer structural metal films through magnetron sputtering alternating deposition process is solved, and the performance degradation of traditional nanocrystalline metal films under fatigue loading is achieved, achieving high conductivity and excellent fatigue resistance.

CN119465037APending Publication Date: 2025-02-18XI AN JIAOTONG UNIV

Patent Information

Application Number
CN202411636396.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Traditional nanocrystalline metal films are prone to fatigue damage under the action of cyclic loads, resulting in degradation or failure of electrical functions. The prior art is difficult to effectively suppress the initiation and expansion of fatigue cracks.

Method used

Ag/Al gradient nanomultilayer structural metal film is prepared by magnetron sputtering alternating deposition process, controlling abnormal grain growth, delaying the invasion of fatigue cracks and suppressing fatigue cracks, and improving the fatigue performance of nanocrystalline metal films.

Benefits of technology

Effective suppression of fatigue crack initiation and expansion is achieved, significantly improving the fatigue life of the film, and maintaining high conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465037A_ABST
    Figure CN119465037A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-fatigue Ag / Al gradient nano multilayer structure metal film and a preparation method, and belongs to the field of material surface modification.The metal film comprises Ag layers and Al layers which are alternately arranged, the grain morphology of the Ag layers is columnar crystals, and the Al layers are of a face-centered cubic structure; the Ag / Al interface is a complete coherent interface and presents a cube-cube orientation relationship; the thicknesses of all Al layers in the Ag / Al gradient nano multi-layer structure metal film are consistent, and the thicknesses of all Ag layers are sequentially increased, sequentially decreased or increased and then decreased. According to the preparation method, the metal thin film is prepared through a magnetron sputtering alternate deposition process, abnormal growth of crystal grains is controlled, fatigue crack initiation is delayed, fatigue crack propagation is inhibited, the fatigue performance of the nanocrystalline metal thin film is improved, effective inhibition of fatigue crack initiation and propagation is achieved, and then the fatigue life of the thin film is greatly prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material surface modification, and in particular relates to an anti-fatigue Ag / Al gradient nano multilayer structure metal film and a preparation method thereof. Background Art

[0002] In recent years, with the continuous advancement of new materials and new process technologies, the flexible electronics industry has ushered in rapid development, and its application scope has expanded to multiple fields such as consumer electronics, energy and environment, medical health, and aerospace. Among them, flexible conductor materials with high conductivity and good mechanical flexibility are the key to achieving the performance of flexible electronic products. In particular, nanocrystalline metal films such as gold (Au), copper (Cu), and silver (Ag) have excellent conductivity (more than 10 7 S m −1 ) and excellent mechanical deformation ability, it has become an ideal choice for manufacturing flexible electrodes. However, in practical applications, these flexible metal films often suffer fatigue damage under cyclic loads such as stretching, bending and torsion, resulting in reduced electrical function or even failure. Therefore, the development of metal films with excellent fatigue resistance is of great practical significance for the sustainable development of the flexible electronics industry.

[0003] Conventional nanocrystalline metal films usually exhibit poor fatigue performance, mainly because their microstructure has limited resistance to fatigue crack initiation and propagation. Fatigue cracks tend to initiate in areas where grains grow abnormally, and rapidly propagate along nanocrystalline grain boundaries, eventually leading to fatigue failure. If the abnormal grain growth can be controlled, fatigue crack initiation can be delayed, and fatigue crack propagation can be inhibited, it is expected to improve the fatigue performance of nanocrystalline metal films and enhance the service stability of flexible electronic devices. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a fatigue-resistant Ag / Al gradient nano-multilayer structure metal film and a preparation method. The method prepares the metal film through a magnetron sputtering alternating deposition process, controls the abnormal grain growth, delays the initiation of fatigue cracks and inhibits the propagation of fatigue cracks, improves the fatigue performance of the nanocrystalline metal film, achieves effective inhibition of the initiation and propagation of fatigue cracks, and thereby greatly improves the fatigue life of the film.

[0005] The present invention is achieved through the following technical solutions: A fatigue-resistant Ag / Al gradient nano multilayer structure metal film comprises alternately arranged Ag layers and Al layers, wherein the Ag layer has a columnar crystal grain morphology and the Al layer has a face-centered cubic structure; the Ag / Al interface is a completely coherent interface and presents a cubic-cubic orientation relationship.

[0006] Preferably, the thickness of each Al layer in the Ag / Al gradient nano multilayer structure metal film is consistent, and the thickness of each Ag layer presents a gradient change.

[0007] Preferably, the thickness of each Ag layer in the Ag / Al gradient nano multilayer structure metal film decreases from top to bottom, increases from top to bottom, or increases first and then decreases.

[0008] Preferably, the Al layer has a thickness of 2-8 nm.

[0009] Preferably, the fatigue performance of the Ag / Al gradient nano multilayer structure metal film is better than that of the Ag single layer film and the Ag / Al multilayer film of equal thickness. 6 The resistance change after tensile fatigue loading can be as low as less than 5%.

[0010] A method for preparing a fatigue-resistant Ag / Al gradient nano multilayer structure metal film comprises the following steps: In a vacuum environment, a DC magnetron sputtering process is used to alternately deposit Ag layers and Al layers on a substrate. The deposition time of each Al layer is the same, and the deposition time of each Ag layer is different or the same depending on the set layer thickness, until the set number of layers is reached and the layer is cooled to room temperature to obtain an Ag / Al gradient nano-multilayer structure metal film.

[0011] Preferably, a Ag target and an Al target are used for DC alternating sputtering, the sputtering power of the Ag target is 120 W, and the sputtering power of the Al target is 200 W.

[0012] Preferably, the sputtering time of the Al layer is 20-80 s, the sputtering rate of the Ag target is 0.36 nm / s, and the sputtering time of the Ag layer is 84-1389 s.

[0013] Preferably, the deposition gas pressure during the magnetron sputtering process is 0.5 Pa.

[0014] Preferably, the substrate rotation speed during the magnetron sputtering process is 15 r / min.

[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The fatigue-resistant Ag / Al gradient nano-multilayer structure metal film of the present application, by coupling the performance advantages of heterogeneous layered structure and gradient structure, and combining fine heterogeneous interface regulation, successfully prepared a uniform and dense Ag / Al gradient nano-multilayer structure metal film with strong film-base bonding strength by using magnetron sputtering alternating deposition process. Thanks to the careful microstructure design, the Ag / Al gradient nano-multilayer structure film not only maintains high conductivity, but also the unique gradient layered design makes it possible to effectively suppress the initiation and propagation of fatigue cracks in the film, thereby significantly improving the fatigue performance of the film.

[0016] The preparation method of the present invention relates to a magnetron sputtering double-target alternating deposition technology, which ensures the uniformity and density of the film by precisely controlling the sputtering parameters. The substrate surface is strictly cleaned and pretreated to ensure good bonding between the film and the substrate. During the deposition process, the substrate rotates at a constant speed of 15 r / min to ensure uniform deposition of the film. Finally, the film is naturally cooled to room temperature in a high vacuum environment to ensure the uniformity of the film's structure and minimization of defects. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0018] Figure 1 Schematic diagram of the gradient laminated structure of Ag / Al films with different gradient structures in the present invention.

[0019] Figure 2 TEM cross-sectional photographs of Ag / Al films with different gradient structures according to the present invention and corresponding grain size distribution diagrams.

[0020] Figure 3 It is a HAADF-STEM photo of the Ag / Al gradient nano multilayer structure metal film of the present invention and a schematic diagram of the interface atomic structure.

[0021] Figure 4 The graph is a curve showing the relative change in resistance of the Ag / Al gradient nano multilayer structure metal film according to the present invention as a function of fatigue cycles. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The components of the embodiments of the present application described and shown in the drawings here can be arranged and designed in various different configurations.

[0023] Therefore, the following detailed description of the embodiments of the present application provided in the accompanying drawings is not intended to limit the scope of the present application for which protection is sought, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0024] A fatigue-resistant Ag / Al gradient nano-multilayer structure metal film, the total thickness of which is 1006 nm, comprises alternately arranged Ag layers and Al layers, the grain morphology of the Ag layer is columnar crystal, and the Al layer is a face-centered cubic structure; the Ag / Al interface is a completely coherent interface, presenting a cubic-cubic orientation relationship.

[0025] In some embodiments, the thickness of each Al layer in the Ag / Al gradient nano-multilayer structure metal film is consistent, and the thickness of the Al layer is 2-8 nm; the thickness of each Ag layer is different, and the thickness of the Ag layer is 30-500 nm.

[0026] In some embodiments, the thickness of the Al layer is constant at 2-8 nm, and the thickness of the Ag layer presents a gradient change; the increase in the thickness gradient of the Ag layer is greater than or equal to 30 nm, the minimum thickness of the Ag layer is 30 nm, the maximum thickness is 500 nm, and the in-plane grain size and out-of-plane grain size of the Ag layer both present a gradient change.

[0027] In some embodiments, the thickness of the Ag layer increases gradually, decreases gradually, or increases first and then decreases from the substrate to the surface.

[0028] The Ag / Al gradient nanostructured multilayer metal film was subjected to a fatigue strain amplitude of 0.7% and a fatigue stress of 1×10 6 The resistance change after tensile-tensile fatigue loading can be as low as 5%.

[0029] The fatigue-resistant Ag / Al gradient nanostructured multilayer metal film of the present application has a high lattice constant match between the Ag and Al layers ( a Ag = 0.409 nm; a Al =0.405 nm), and their identical face-centered cubic structure, promote the formation of Ag / Al heterogeneous coherent interface. This interface structure exhibits excellent stability under cyclic loading, dislocations easily pass through the interface, effectively coordinating the deformation on both sides, thereby significantly improving the fatigue resistance of the film. In addition, the elastic modulus of Ag and Al are similar ( E Ag =83GPa; E Al=70 GPa), and the small modulus mismatch makes the interface less susceptible to damage during fatigue. The stability of this interface is crucial to limiting the abnormal growth of Ag layer grains. Through the constraint of the Ag / Al interface, the growth of Ag layer grains is effectively controlled within the layer, thereby maintaining the integrity of the gradient layered structure and delaying the initiation of fatigue cracks. The design of the Ag / Al gradient nano-multilayer structure plays a key role in the fatigue crack propagation process. When the fatigue crack propagates to the interface, due to the low interface bonding strength of the Ag / Al interface itself (1.4 J m -2 ) and the complex stress field at the crack tip caused by the gradient structure, the fatigue crack tends to deflect to the Ag / Al interface, causing interface debonding. This crack deflection behavior consumes the plastic deformation energy well and avoids the destruction of the conductive path of the film, thereby ensuring that the change of film resistance remains at a low level. The conductivity of the film is as high as 3.1×10 7 S m −1 The unique Ag / Al gradient layered structure design makes the film exhibit excellent anti-fatigue design, realizing the excellent electrical conductivity and anti-fatigue properties of the alloy film.

[0030] Correspondingly, the present application also provides a method for preparing a fatigue-resistant Ag / Al gradient nano multilayer structure metal film, comprising the following process: In a vacuum environment, a DC magnetron sputtering process is used to alternately deposit Ag layers and Al layers on a substrate. The deposition time of each Al layer is the same, and the deposition time of each Ag layer is different or the same depending on the set layer thickness, until the set number of layers is reached and the layer is cooled to room temperature to obtain an Ag / Al gradient nano-multilayer structure metal film.

[0031] During the preparation process, the substrate needs to be cleaned and dried first, then the treated substrate is etched, and then the target material is pre-sputtered for a certain period of time to remove the adsorbed substances on the surface of the target material. Finally, DC magnetron sputtering is performed on the etched and cleaned substrate to deposit the Ag layer and Al layer.

[0032] In some embodiments, the etching and pre-sputtering method of the substrate is as follows: The cleaned polyimide substrate is fixed on the base plate and sent into the coating chamber, and then the vacuum degree of the back of the chamber is pumped to 4.0×10 -4 Pa or less, using Ar + Ions are used for etching and cleaning to further remove impurities on the substrate surface. The etching power is 200 W, the etching argon pressure is 0.5 Pa, and the etching time is 5 min.

[0033] Then pre-sputtering was performed. Before pre-sputtering, argon gas was introduced for 30 s with an argon flow rate of 40 sccm. Then pre-sputtering was performed for 30 s to remove adsorbed substances on the surface of the target material.

[0034] In the formal sputtering process, direct current Ag target and Al target were used to alternately sputter and deposit Ag layer and Al layer. The sputtering power of Ag target was 120 W, the sputtering power of Al target was 200 W, the deposition gas pressure was 0.5 Pa, and the substrate rotation speed was fixed at 15 r / min during the alternating sputtering deposition process. The sputtering rate of Al target was 0.1 nm / s, the sputtering time of Al layer was 20-80 s, the sputtering rate of Ag target was 0.36 nm / s, and the sputtering time of Ag layer was 84-1389 s.

[0035] This application prepares Ag / Al gradient nano-multilayer films through a magnetron sputtering alternating deposition process. The preparation method is simple, cost-effective, and easy to scale up for production. It provides a high-performance electrode material solution for the flexible electronics industry, which can effectively solve the fatigue problem of flexible metal films in the prior art and promote the development and application of flexible electronics technology.

[0036] Example 1 A method for preparing a fatigue-resistant Ag / Al gradient nano multilayer structure metal film comprises the following steps: Step 1: ultrasonically clean the polyimide substrate in anhydrous ethanol for 15 min and then quickly dry it to make the surface of the polyimide substrate clean and free of impurities.

[0037] Step 2: Fix the cleaned polyimide substrate on the base plate and put it into the coating chamber, and then draw the back vacuum to 4.0×10 -4 Pa to remove impurities on the surface of the polyimide substrate. The etching power was 200 W, the etching pressure was 0.5 Pa, and the time was 5 min.

[0038] Step 3: Using DC magnetron sputtering to alternately deposit Ag / Al gradient nano multilayer structure films.

[0039] First, argon gas was introduced for 30 s to reach the working gas pressure, and the target material was pre-sputtered for 30 s. High-purity Ag target (purity of 99.995 wt.%) and Al target (purity of 99.999 wt.%) were used to alternately deposit Ag layer and Al layer. The deposition powers were 120 W and 200 W, respectively, the substrate rotation speed was 15 r / min, the deposition pressure was set to 0.5 Pa, the argon flow rate was 40 sccm, and the deposition was carried out at room temperature. A total of 4 Al layers were sputtered as the intermediate layer, and the thickness of each layer was fixed at 4 nm. The Al intermediate layer separated the Ag layer into 5 layers in total. The thickness of the Ag layer increased monotonically from the surface to the substrate, showing a gradient change.

[0040] The sputtering rate of the Al target is 0.1 nm / s, and the sputtering time of each Al layer is the same, which is 40 s. The thickness of the deposited Al layers is the same, all of which are 4 nm. The sputtering rate of the Ag target is 0.36 nm / s, and the sputtering time of each Ag layer is the same and increases successively, which is 84 s, 167 s, 417 s, 695 s and 1389 s respectively. The thickness of each Ag layer obtained is 30 nm, 60 nm, 150 nm, 250 nm and 500 nm. The total sputtering time is 2912 s, and the total film thickness of the Ag / Al gradient nano-multilayer structure metal film is 1006 nm.

[0041] Step 4: After the sample is naturally cooled in the vacuum coating chamber for 1 hour to room temperature, it is taken out to obtain a Ag / Al gradient nano multilayer structure film with a thickness of about 1 μm.

[0042] The microstructure of the prepared Ag / Al gradient nano-multilayer structure film was characterized. The Ag layer grains showed a columnar crystal structure, and the grain size increased from the surface to the substrate, which was consistent with the trend of layer thickness change. The Al intermediate layer was a face-centered cubic structure, and the Ag / Al interface was a coherent interface with a cubic-cubic orientation relationship.

[0043] Example 2 A method for preparing a fatigue-resistant Ag / Al gradient nano multilayer structure metal film comprises the following steps: Step 1: ultrasonically clean the polyimide substrate in anhydrous ethanol for 15 min and then quickly dry it to make the surface of the polyimide substrate clean and free of impurities.

[0044] Step 2: Fix the cleaned polyimide substrate on the base plate and put it into the coating chamber, and then draw the back vacuum to 4.0×10 -4 Pa to remove impurities on the surface of the polyimide substrate. The etching power was 200 W, the etching pressure was 0.5 Pa, and the time was 5 min.

[0045] Step 3: Using DC magnetron sputtering to alternately deposit Ag / Al gradient nano multilayer structure films.

[0046] First, argon gas was introduced for 30 s to reach the working gas pressure, and the target material was pre-sputtered for 30 s. High-purity Ag target (purity of 99.995 wt.%) and Al target (purity of 99.999 wt.%) were used to alternately deposit Ag layer and Al layer. The deposition powers were 120 W and 200 W, respectively, the substrate rotation speed was 15 r / min, the deposition pressure was set to 0.5 Pa, the argon flow rate was 40 sccm, and the deposition was carried out at room temperature. A total of 4 Al layers were sputtered as the intermediate layer, and the thickness of each layer was fixed at 4 nm. The Al intermediate layer separated the Ag layer into 5 layers in total. The thickness of the Ag layer decreased monotonically from the surface to the substrate, showing a gradient change.

[0047] The sputtering rate of the Al target is 0.1 nm / s, and the sputtering time of each Al layer is the same, which is 40 s. The thickness of the deposited Al layers is the same, all of which are 4 nm. The sputtering rate of the Ag target is 0.36 nm / s, and the sputtering time of each Ag layer is the same and decreases in sequence, which is 1389 s, 695 s, 417 s, 167 s and 84 s respectively. The thickness of each Ag layer is 500 nm, 250 nm, 120 nm, 60 nm and 30 nm. The total sputtering time is 2912 s, and the total film thickness of the Ag / Al gradient nano-multilayer structure metal film is 1006 nm.

[0048] Step 4: After the sample is naturally cooled in the vacuum coating chamber for 1 hour to room temperature, it is taken out to obtain a Ag / Al gradient nano multilayer structure film with a thickness of about 1 μm.

[0049] The microstructure of the prepared Ag / Al gradient nano-multilayer structure film was characterized. The Ag layer grains showed a columnar crystal structure, and the grain size decreased from the surface to the substrate, which was consistent with the trend of layer thickness change. The Al intermediate layer was a face-centered cubic structure, and the Ag / Al interface was a coherent interface with a cubic-cubic orientation relationship.

[0050] Example 3 A method for preparing a fatigue-resistant Ag / Al gradient nano multilayer structure metal film comprises the following steps: Step 1: ultrasonically clean the polyimide substrate in anhydrous ethanol for 15 min and then quickly dry it to make the surface of the polyimide substrate clean and free of impurities.

[0051] Step 2: Fix the cleaned polyimide substrate on the base plate and put it into the coating chamber, and then draw the back vacuum to 4.0×10 -4 Pa to remove impurities on the surface of the polyimide substrate. The etching power was 200 W, the etching pressure was 0.5 Pa, and the time was 5 min.

[0052] Step 3: Using DC magnetron sputtering to alternately deposit Ag / Al gradient nano multilayer structure films.

[0053] First, argon gas was introduced for 30 s to reach the working gas pressure, and the target material was pre-sputtered for 30 s. High-purity Ag target (purity of 99.995 wt.%) and Al target (purity of 99.999 wt.%) were used to alternately deposit Ag layer and Al layer. The deposition powers were 120 W and 200 W, respectively, the substrate rotation speed was 15 r / min, the deposition pressure was set to 0.5 Pa, the argon flow rate was 40 sccm, and the deposition was carried out at room temperature. A total of 4 Al layers were sputtered as the intermediate layer, and the thickness of each layer was fixed at 4 nm. The Al intermediate layer separated the Ag layer into 5 layers in total. The thickness of the Ag layer increased first and then decreased from the surface to the substrate.

[0054] The sputtering rate of the Al target is 0.1 nm / s, and the sputtering time of each Al layer is the same, which is 40 s. The thickness of the deposited Al layers is the same, all of which are 4 nm. The sputtering rate of the Ag target is 0.36 nm / s, and the sputtering time of each Ag layer increases first and then decreases, which are 84 s, 598 s, 1389 s, 598 s and 84 s, respectively. The thickness of each Ag layer obtained is 30 nm, 215 nm, 500 nm, 215 nm and 30 nm. The total sputtering time is 2913 s, and the total film thickness of the Ag / Al gradient nano-multilayer structure metal film is 1006 nm.

[0055] Step 4: After the sample is naturally cooled in the vacuum coating chamber for 1 hour to room temperature, it is taken out to obtain a Ag / Al gradient nano multilayer structure film with a thickness of about 1 μm.

[0056] The microstructure of the prepared Ag / Al gradient nano-multilayer structure film was characterized. The Ag layer grains showed a columnar crystal structure, and the grain size first increased and then decreased from the surface to the substrate, which was consistent with the trend of layer thickness change. The Al intermediate layer had a face-centered cubic structure, and the Ag / Al interface was a coherent interface with a cubic-cubic orientation relationship.

[0057] Comparative Example 1 The difference between Comparative Example 1 and Examples 1-3 is that no Al intermediate layer is added, and a common single-layer Ag film is used, wherein the film deposition rate is 0.36 nm / s, the deposition time is 2778 s, and the obtained Ag layer thickness is 1000 nm. The rest of the method is the same as Examples 1-3.

[0058] Comparative Example 2 The difference between this comparative example 1 and examples 1-3 is that the thickness of the Ag layer is the same and there is no gradient change. It is a homogeneous Ag / Al multilayer metal film, wherein the deposition rates of Ag and Al are 0.36 nm / s and 0.1 nm / s respectively, there are 5 Ag layers in total, the sputtering time of each layer is 556 s, and the corresponding thickness of each Ag film is 200 nm; there are 4 Al layers in total, the sputtering time of each layer is 40 s, and the corresponding thickness of each Ag film is 4 nm; the total sputtering time of the film is 2940 s, and the total thickness of the film is 1016 nm. The rest of the methods are the same as those of examples 1-3.

[0059] Comparative Example 3 The difference between this comparative example and Examples 1-3 is that the thickness of the Ag layer is the same and there is no gradient change. It is a homogeneous Ag / Al multilayer metal film, in which the deposition rates of Ag and Al are 0.36 nm / s and 0.1 nm / s, respectively. There are 33 Ag layers in total, and the sputtering time for each layer is 84 s, corresponding to a thickness of each Ag film of 30 nm; there are 32 Al layers in total, and the sputtering time for each layer is 40 s, corresponding to a thickness of each Ag film of 4 nm; the total sputtering time of the film is 4052 s, and the total thickness of the film is 1006 nm. The rest of the methods are the same as Examples 1-3.

[0060] Figure 1 Schematic diagrams of Ag / Al laminated structures of Examples 1-3 and Comparative Examples 1-3 are shown. Figure 2 and Figure 3 The TEM images of Ag / Al gradient nanolayered films prepared by DC magnetron sputtering alternating deposition technology and high-resolution atomic images of the Ag / Al interface are shown. These images reveal the microstructural features of the film and prove the successful preparation of the gradient nanolayered structure and the formation of the heterogeneous coherent interface. Figure 4 The fatigue-resistance curve of the Ag / Al gradient nanolayered structure film is shown. The fatigue loading strain amplitude is 0.7% and the loading mode is tension-tension fatigue. The test results show that the film of the present invention exhibits excellent electrical stability and outstanding fatigue performance under cyclic loading.

[0061] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A fatigue-resistant Ag / Al gradient nano-multilayered metal film, characterized in that: It comprises Ag layers and Al layers which are alternately arranged, wherein the grain morphology of the Ag layer is columnar crystal, and the Al layer is a face-centered cubic structure; the Ag / Al interface is a completely coherent interface, presenting a cubic-cubic orientation relationship.

2. The anti-fatigue Ag / Al gradient nano multilayer structure metal film according to claim 1, characterized in that: The thickness of each Al layer in the Ag / Al gradient nano multilayer structure metal film is consistent, and the thickness of each Ag layer presents a gradient change.

3. The fatigue-resistant Ag / Al gradient nano multilayer structure metal film according to claim 1, characterized in that: The thickness of each Ag layer in the Ag / Al gradient nano multilayer structure metal film decreases from top to bottom, increases from top to bottom, or increases first and then decreases.

4. The anti-fatigue Ag / Al gradient nano multilayer structure metal film according to claim 1, characterized in that: The thickness of the Al layer is 2-8 nm.

5. The fatigue-resistant Ag / Al gradient nano multilayer structure metal film according to claim 1, characterized in that: The fatigue properties of the Ag / Al gradient nanostructured multilayer metal film are better than those of the Ag single layer film and the Ag / Al multilayer film with equal thickness. 6 The resistance change after tensile fatigue loading can be as low as less than 5%.

6. The method for preparing a fatigue-resistant Ag / Al gradient nano multilayer structure metal film according to any one of claims 1 to 5, characterized in that: The process includes: In a vacuum environment, a DC magnetron sputtering process is used to alternately deposit Ag layers and Al layers on a substrate. The deposition time of each Al layer is the same, and the deposition time of each Ag layer is different or the same depending on the set layer thickness, until the set number of layers is reached and the layer is cooled to room temperature to obtain an Ag / Al gradient nano-multilayer structure metal film.

7. The method for preparing a fatigue-resistant Ag / Al gradient nano multilayer structure metal film according to claim 6, characterized in that: Ag target and Al target were used for DC alternating sputtering. The sputtering power of Ag target was 120 W, and the sputtering power of Al target was 200 W.

8. The method for preparing the fatigue-resistant Ag / Al gradient nano multilayer structure metal film according to claim 7, characterized in that: The sputtering time of the Al layer is 20-80 s, the sputtering rate of the Ag target is 0.36 nm / s, and the sputtering time of the Ag layer is 84-1389 s.

9. The method for preparing a fatigue-resistant Ag / Al gradient nano multilayer structure metal film according to claim 6, characterized in that: The deposition gas pressure during the magnetron sputtering process is 0.5 Pa.

10. The method for preparing a fatigue-resistant Ag / Al gradient nano multilayer structure metal film according to claim 6, characterized in that: The substrate rotation speed during the magnetron sputtering process is 15 r / min.

Citation Information

Patent Citations

  • Method for preparing coherent / semi-coherent structural Al / W multilayer film

    CN102409309A

  • Method for improving toughness of nano-metal multilayer film

    CN111020513A

  • Copper-silver alloy film and preparation method and application thereof

    CN116988031A

  • Method for Producing High Stacking Fault Energy (SFE) Metal Films, Foils, and Coatings with High-Density Nanoscale Twin Boundaries

    US20150233019A1

Cited By

  • Anti-fatigue gradient Ag multilayer structure metal film and preparation method and application thereof

    CN121137524A